Heavy Metal Removal Investigation in Conventional Activated Sludge Systems - Magdi Buaisha; Saziye Balku; Şeniz Özalp Yaman (Civil Engineering Journal, 2020)
The combination of industrial and domestic wastewater in municipal WWTPs (waste water treatment plants) may be economically profitable, but it increases the difficulty of treatment, and also has some detrimental effects on the biomass and causes a low-quality final effluent. The present study evaluates the treatment process both in the presence and absence of heavy metals using ASM3 (activated sludge model no.3) so as to improve the model by means of incorporating other novel inhibitory kinetic and settler models. The results reveal that the presence of heavy metal, a case study for copper and cadmium at a concentration of 0.7 mgL−1 in a biological treatment system has a negative effect on heterotrophic bacteria concentration by 25.00 %, and 8.76 % respectively. Meanwhile, there are no important changes in COD (chemical oxygen demand), SS (total suspended solids) and TN (total nitrogen) in the final effluent in the conventional system. However, all these parameters are acceptable and consistent with EU Commission Directives. The results indicate that ASM3 can predict and provide an opportunity of the operation for an activated sludge wastewater treatment plant that receives the effluent from an industrial plant.